Menganalisis Dilema Masalah Penduduk Sebagai Penghambat Pembangunan Atau Pendorong Pembangunan - Achmad Faris Fizabillah; Silvia Damayanti; Muhammad Yasin (Universitas 45 Surabaya, 2024)
This research aims to analyze the dilemma of population problems which can act as an obstacle or driver of development. In this study, demographic factors such as population growth, population distribution, and socio-economic dynamics are evaluated to understand their impact on the development process. Through qualitative methods, this research collects and analyzes secondary data from various sources, including population reports, development studies, and academic literature. The research results show that population conditions can become an obstacle when population growth is not balanced with infrastructure and resource capacity. However, with proper management, population can also be a driver of development through optimizing the workforce and increasing productivity. The conclusion of this research emphasizes the importance of adaptive and data-based policy strategies to overcome population dilemmas in the context of sustainable development.